Environmental Ethics Vol. 11 No. 2 - Rhyddhi Chakraborty (Bangladesh Journal of Bioethics)
Cambridge online dictionary offers the meaning of the noun term “environment” as the air, water, and land in or on which humans, animals, and plants reside1. The environment can also be a mixture of factors that influence both organic and inorganic ecosystems and their shared co- existence. This co-existence is the last idea that is given significance in the sophisticated and busy life styles of the modern day.